The rise of China and the time of Africa: Gauging Afro-Sino relations in the light of Confucian philosophy and African ideals - Du Toit, Cornel W. (HTS teologiese studies, 2015)
The article focuses on Sino-African relations, with specific reference to South Africa. An outline is provided of recent developments as a roadmap for the unfolding of this relationship. The question of whether China’s African interest can be seen as tacit colonisation is discussed. Even if these fears are allayed, the question remains whether the Chinese presence on the continent will make a significant difference to African development. To answer this question, the focus shifts to economic models and the Chinese recipe for economic progress. Confucianism was opposed during the cultural revolution of Mao Zedong, but it now forms the basis for Chinese foreign policy and internal affairs. This is briefly investigated. Some Confucian ideas are related to basic African concepts in an effort to find a common ground in Afro-Chinese relations. The impact of secular Confucianism on African spirituality is discussed.